Screening for pelvic floor symptoms in exercising women: a survey of 636 health and exercise professionals. Issue 2 (February 2023) - Dakic, Jodie G.; Hay-Smith, Jean; Cook, Jill; Lin, Kuan-Yin; Frawley, Helena C.
Abstract: Objectives: This study aimed to establish health and exercise professionals' (i) current practice of screening for pelvic floor (PF) symptoms in women within sports/exercise settings (ii) between-professional group differences in screening practice (iii) confidence and attitudes towards screening for PF symptoms and (iv) barrier/enablers towards engagement in future screening practice. Design: Observational, cross-sectional survey. Methods: Australian health and exercise professionals (n = 636) working with exercising women participated in a purpose-designed and piloted, online survey about PF symptom screening in professional practice. Data were analysed descriptively and groups compared using Chi-square/Kruskal-Wallis tests. Results: Survey respondents included physiotherapists (39%), personal trainers/fitness instructors (38%) and exercise physiologists (12%), with a mean of 12 years of practice (SD: 9.7, range: 0–46). One in two participants never screened women for PF symptoms; 23% screened when indicated. Pregnant/recently post-natal women (44%) were more commonly screened for PF symptoms than younger women (18–25 years:28%) and those competing in high-impact sports (32%). Reasons for not screening included waiting for patients to disclose symptoms (41%) and an absence of PF questions on screening tools (37%). Most participants were willing to screen PF symptoms but cited a lack of knowledge, training and confidence as barriers. Conclusions: Screening for PF symptoms in exercising women is not common practice, especially in at-risk groups such as young, high-impact athletes. Including PF questions in existing pre-exercise questionnaires and providing professional development to improve knowledge of indications for screening and evidence-based management options may facilitate early symptom identification and prevent secondary exercise cessation.